2019
DOI: 10.3389/fpls.2019.01348
|View full text |Cite
|
Sign up to set email alerts
|

GhTIE1 Regulates Branching Through Modulating the Transcriptional Activity of TCPs in Cotton and Arabidopsis

Abstract: Transcription factors (TFs) and transcriptional regulators are important switches in transcriptional networks. In recent years, the transcriptional regulator TIE1 (TCP interactor containing EAR motif protein 1) was identified as a nuclear transcriptional repressor which regulates leaf development and controls branch development. However, the function and regulatory network of GhTIE1 has not been studied in cotton. Here, we demonstrated that GhTIE1 is functionally conserved in controlling shoot branching in cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…TIE1 had overlapping expression pattern with BRC1 in young axillary buds and overexpression of TIE1 resulted in excessive branches, indicating that TIE1 also represses the activity of BRC1 during shoot branching [ 40 ]. The function of TIE1 is conserved in controlling shoot branching in cotton ( Gossypium hirsutum ) [ 117 ]. GhTIE1 interacted with CYC subclade proteins GhBRC1, GhBRC2, and GhTCP13 in vivo.…”
Section: Chromatin Remodeling Complexes Regulate the Activity Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…TIE1 had overlapping expression pattern with BRC1 in young axillary buds and overexpression of TIE1 resulted in excessive branches, indicating that TIE1 also represses the activity of BRC1 during shoot branching [ 40 ]. The function of TIE1 is conserved in controlling shoot branching in cotton ( Gossypium hirsutum ) [ 117 ]. GhTIE1 interacted with CYC subclade proteins GhBRC1, GhBRC2, and GhTCP13 in vivo.…”
Section: Chromatin Remodeling Complexes Regulate the Activity Of Cmentioning
confidence: 99%
“…GhTIE1 interacted with CYC subclade proteins GhBRC1, GhBRC2, and GhTCP13 in vivo. Silencing of GhTIE1 in cotton seriously decreased shoot branching [ 117 ]. A similar mechanism in suppression of CIN-like TCP activity is mediated by SPOROCYTELESS/NOZZLE (SPL/NZZ) during ovule development [ 118 ].…”
Section: Chromatin Remodeling Complexes Regulate the Activity Of Cmentioning
confidence: 99%
“…In rice, the moc1 mutant failed to develop tillers due to defects in axillary meristem formation, which is similar to the ls mutant tomato phenotype (Li et al., 2003 ; Schumacher et al., 1999 ). TIE1 promoted cotton branching via repressing the transcription activity of TCPs (Diao et al., 2019 ). Mutation of SP homologs promoted short‐branching architecture in cotton, and dynamic changes in GhSFT and GhSP expression level regulated cotton monopodial and sympodial branching architecture (McGarry et al., 2016 ; Si et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show that GhCUC2 is cleaved by gh‐miR164, and that GhCUC2 with mutated target sequence could not be cleaved by miR164. GhCUC2 physically interacts with a previously known lateral branch development‐related protein GhBRC1 and activates its transcriptional activity to regulate lateral branch development (Diao et al., 2019 ). In addition, genetic analysis demonstrated that GhCUC2 and GhBRC1 negatively regulate branching, exerting the opposite effect of miR164.…”
Section: Introductionmentioning
confidence: 99%
“…Another class I TCP, GbTCP of G. barbadense, affects fiber elongation through a complex interplay involving jasmonic acid biosynthesis and ethylene signaling (Hao et al, 2012). GhTCP13 and two other class II TCPs are functionally redundant in modulating plant architecture (Diao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%